Thomas' Calculus 13th Edition

Published by Pearson
ISBN 10: 0-32187-896-5
ISBN 13: 978-0-32187-896-0

Chapter 1: Functions - Additional and Advanced Exercises - Page 38: 4



Work Step by Step

Given $g(x)$ is an odd function, we have $g(-x)=-g(x)$. Let $x=0$, we have $g(-0)=-g(0)$ or $g(0)=-g(0)$ which leads to $2g(0)=0$ and $g(0)=0$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.